Analisis Gaya Bahasa Dalam Cerita Rakyat Oleh Siswa Kelas X SMAN I Damang Batu Serta Implikasinya Terhadap Pembelajaran Sastra Di SMA - Misnawati Misnawati; Ngangga Saputra; Siti Muslimah; Anwarsani Anwarsani; Siti Rahmawati; Nabila Salwa (Pusat Riset dan Inovasi Nasional, 2023)
The purpose of this research is to describe the forms of language style in the Central Kalimantan folktales by the 10th-grade students of SMAN I Damang Batu and to investigate their implications for literature learning in high schools. The research technique used was qualitative descriptive research with content analysis. Based on the analysis conducted by the author, the research findings revealed the existence of language style in the Central Kalimantan folktales by the 10th-grade students of SMAN I Damang Batu, namely emotive language style with four quotes, connotative meaning with four quotes, hyperbole with four quotes, metaphor with five quotes, and personification with five quotes. Therefore, the dominant language style used in the Central Kalimantan folktales by the 10th-grade students of SMAN I Damang Batu is the metaphor and personification style.